The Effect Of Inflation, Interest Rates And Capital Structure On Share Prices In Manufacturing Companies (Food And Beverage Sub-Sector Listed On The Indonesian Stock Exchange For The 2019-2022 Period) - Akbar, Robillah; Pertiwi, Dinal Eka (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This research aims to determine the effect of inflation, interest rates and capital structure on share prices in food and beverage sub-sector manufacturing companies listed on the Indonesian Stock Exchange for the 2019-2022 period. The population obtained in the research were food and beverage sub-sector manufacturing companies listed on the Indonesian Stock Exchange for the 2019-2022 period. The research samples obtained were 36. The sample collection technique used purposive sampling. The method in this research is a quantitative method. This research uses multiple linear regression analysis using SPSS V25 software. The results of this research show that inflation and capital structure have no effect on stock prices, while interest rates have an effect on stock prices.